A prática da educação étnico-racial : um estudo da implantação da Lei Federal 10.639/03 no Paraná a partir do professor como leitor do livro didático público - Caten, Artemio Ten (2010)
In this work, we present the research results about the Federal Law 10.639/03, which modifies the LDB - Law of Education Directives and Bases: 9394/96, including the obligation of the subject Afro-Brazilians and Africans history and culture in the official syllabuses of basic education. Specifically, we sought to determine which settings the integration of such content has taken place in high school located in the City of Toledo / PR. We analyze aspects of differences and contradictions between educational legislation about racism and the social and school practice that reproduces and justifies the racial discrimination. We ponder that this law indication impacts on the education of History centered in Eurocentric narratives, followed by a stereotyped approaching of the Afro-Brazilians and African History and the Culture and this is paradoxical in relation to the racial discrimination practice in Brazil, which is permeated by a notorious racist approaching, constructed to legitimize the marginalization of the black people. As a result, we investigate the Law implementation and how the relationship is taking place among teachers working in the Paraná State Network for overcoming a Eurocentric curriculum and to seek a reeducation of ethnic-racial relations. Supported by the theoretical referential of Jörn Rüsen, we analyze the approaching of the contents concerning to the Law, in the Public Didactic Book of the Paraná State, High School Education, in the History discipline, and we interviewed the teachers who lection the History discipline in High School, focusing them as readers of those texts that display the contents connected to this Federal Law. In order to understand the speech direction in the interview messages, we use Bardin content analysis, which methodology is composed by three phases: pre-analysis (exhausting reading), the material exploration (to reach the different meaning nucleus) and the results treatment (formularization/regrouping in categories and subcategories).There is a fundamental question for us: on the one hand, the implementation of this law allows a reflection on the racial discrimination and practice and social inequality, on the other hand, we reflect if the inclusion of these contents can corroborate an education conception in the level that is attributed the task of minimizing social problems historically established. We consider that racial discrimination against African-Brazilians do not seems to be an individual construction, made by the person who should be reeducated in the ethnic-racial relations level and, also, in a historical construction of social class related to the exploration at work. We analyze this Law as a legitimate claim of the Black Movement and as a speech incorporated by the State representatives who act forward the maintenance of the capitalist production way. We verify that the actions taken from this Law are restricted because the educator s formation has limits concerning the qualification level for the re-education of the ethnic-racial relations. The interviews pronounce the existence of a fragmented implantation plan of the Law and the actions taken from its application depend on the educators militancy and, also, a more significant social acceptance of the Afro-Brazilians. However, the implementation process of this Law points out to the discussion of the race issue and to analyze the large social gaps existing within schools and the Brazilian social context, even if we do not perceive significant alterations in terms of curricular change.